Initial Coin Offerings (ICOs): The importance of human capital - Campino, J.; Brochado, A.; Rosa, Á. (Research Square, 2021)
The Initial Coin Offerings (ICOs) subject has been gaining relevance due to its novelty, due to the capital amounts involved in the projects, as well as the disruptive technology and methods involved. ICOs are a disruptive way to finance new projects which involve high risks and which are mainly technological. This way to finance a project has been compared to others, namely, crowdfunding, venture capital or Initial Public Offerings (IPOs). Nevertheless, ICOs have very specific characteristics which make them unique. We have studied the ICO projects and developed a literature review on the topic. Building on the Human Capital Theory (HCT), we have also studied the importance given to the project’s team and its perceived impact on projects’ success. Our contribution to fill in this literature gap was to develop an econometric model which measures the impact of team’s characteristics on the success of a project. The database was collected with the combination of two data sources and is composed of 3158 profiles and 340 ICO projects. We have concluded that team variables are significant contributors to project’s success. Our data suggests that people’s location contributes to projects’ success as well as promoters’ networks. The ratings attributed by external parties to the project are also indicators of success. Several control variables such as the implementation of thresholds to investment, the number of currencies accepted, the platform in which the ICO is developed, the existence of bonus schemes and the year of the project were found to be statistically significant having an impact on projects’ outcome.